Analyzing the Generic Structure of Recount Text Written by The Tenth Graders - Anggi Eka Aprilina; Meiga Ratih Tirtanawati; Puput Suriyah (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Writing becomes one of the skills that must be learned by students because by writing they can convey ideas in addition to speaking in written form. This descriptive qualitative research aimed to find the generic structural constructs in the recount texts written by six students in class X IPS 1 at SMAN 1 Kalitidu. The research results indicated that four students mentioned the who, what, when, and where aspects of the orientation, while two students missed two of them. In terms of a series of events, four students wrote a sequence of events by stating the day, clock, and activity, whereas two students did not write the events chronologically. Finally, in the re-orientation part, to end their personal experience, three students wrote summaries, comments, and impressions, but the rest of the students did not. Accordingly, three out of six students composed good recount texts, but the others still needed improvement.